Cytokines and Exocrine Pancreatic Cancer: Is There a Link? - Basso, Daniela; Plebani, Mario (JOP. Journal of the Pancreas, 2016)
No abstract available. Image: Schematic representation of TGFbeta1 signal transduction pathway via Smad proteins.